Platform Business Poses Risks for News Publishers - Myllylahti, Merja; Westlund, Oscar; Chua, Sherwin (Routledge, 2024)
Publishers used to own and control their distribution. With the world wide web, publishers expanded to distribute their news via proprietary news sites. The rise of social media platforms and mobile ecosystems (notably Apple and Android) further added to how publishers distribute and redistribute their news. Publishers have essentially pursued to build platform presence on non-proprietary platforms that are widely popular by the public (and desired user segments), striving towards driving attention and traffic to their brands and proprietary platforms. Audience engagement and ambitions for advertising revenues have been central, yet publishers have painfully experienced substantial online advertising losses. Global platform companies, especially Alphabet and Meta, have successfully taken over most of online advertising. Reader revenue has become an increasingly important revenue stream for publishers, and for many, the most important one. This chapter problematizes the funding of journalism by zooming in on the shifting interrelationships between publishers and platforms. Critical of long-term effects, more and more publishers have engaged in platform counterbalancing, seeking to reduce their dependence on specific non-proprietary platforms by configuring what they do for different platforms. This chapter stresses that both publishers and platforms are marked by heterogeneity and so are their evolving interrelationships and interdependencies. This chapter focuses on the business of journalism amid platforms, discussing differences in approaches to platforms and the funding of journalism. Most publishers engage with platforms to gain attention, traffic, subscriptions, training, tools and revenue. In extension of this, this chapter discusses how platforms take on roles as profiteers and payers and ends with a discussion of four key risk areas for publishers amid platform power.